1991
DOI: 10.1038/bjc.1991.47
|View full text |Cite
|
Sign up to set email alerts
|

Expression of anionic glutathione S transferase (GSTπ) gene in carcinomas of the uterine cervix and in normal cervices

Abstract: SummaryThe aim of the present study was to analyse in invasive carcinomas of the uterine cervix, the anionic glutathione S transferase (GSTi) gene, possibly implicated in the drug resistance of human cancers. Total RNA preparations obtained from invasive cervical cancers (106 specimens), carcinomas in situ (CIS) (three specimens) and normal cervical epitheliums (24 specimens) were analysed by Northern (Pastan & Gottesman, 1987;Moscow & Cowan, 1988;Endicott & Ling, 1989;D'Arpa & Liu, 1989;Beck, 1989;Giovanel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Riou et al [22] reported, on the basis of Northern blot analysis, that although GST-~ is expressed in normal epithelium its expression is enhanced in dysplasia and in carcinoma of the uterine cervix. Also using Northern blot analysis, Konohana et al [13] stated that GST-~ was expressed in the human skin but that no quantitative difference was recognized in the expression of GST-~ between cultured human keratinocytes and the A431 SCC cell line.…”
Section: Discussionmentioning
confidence: 98%
“…Riou et al [22] reported, on the basis of Northern blot analysis, that although GST-~ is expressed in normal epithelium its expression is enhanced in dysplasia and in carcinoma of the uterine cervix. Also using Northern blot analysis, Konohana et al [13] stated that GST-~ was expressed in the human skin but that no quantitative difference was recognized in the expression of GST-~ between cultured human keratinocytes and the A431 SCC cell line.…”
Section: Discussionmentioning
confidence: 98%
“…Moscow et al (22) reported a 7-fold increase in GST-tc mRNA levels in five squamous head and neck cancers as compared with adjacent normal tissue. In addition, Riou et ai (23) found increased levels of GST-ti mRNA in squamous cell carcinomas of the cervix and Eimoto ei ai (24) observed higher GST-ti immunoreactivity in squamous cell carcinomas of the lung when compared with other histological types of lung cancer. In contrast, oesophageal squamous cell carcinomas had lower mean GSTtc concentrations than the surrounding normal tissue, but tumours with much higher GST-tc levels were also found (25).…”
Section: Discussionmentioning
confidence: 99%